Double Certificates and Its Resolution in (Study of Supreme Court Decision Number 976 K/PDT/2015) - Soediro Soediro; Ika Ariani Kartini; Efi Miftah Faridli; Nur’aeni Nur’aeni (Proceedings Series on Social Sciences & Humanities, 2023)
One of the goals of the Basic Agrarian Law (Undang-Undang Pokok Agraria, UUPA) is to provide legal certainty for all individuals and to facilitate the functioning of the earth, water, and space, as well as natural resources. In reality, however, the law has not yet provided legal certainty over land in the case of double certificates, as stated in Supreme Court Decision No. 976 K/PDT of 2015. The problem posed by this study is how and what the obstacles are for prevent the development of duplicate certificates. This is normative legal research employing secondary data, the statute approach, and the conceptual approach. To prevent the occurrence of double certificates, it is necessary to implement a computerization/digitization program for land registration maps to reduce error by humans, acquire data on land parcels that have certificates, make plotting efforts utilizing GPS (Global Positioning System) technology, restrict the land registration process and administration pertaining to village land, and implement blockchain technology in land administration. Meanwhile, the public's lack of interest in registering their land through the Comprehensive Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap, PTSL) scheme, procedural errors in the land assessment procedure, a negative land publication system in which the data presented is not necessarily valid, and the state's inability to guarantee the accuracy of the data presented are impediments to these efforts. Moreover, the present agrarian law is a colonialist relic that is not in the community's best interests.